Lipase-catalyzed synthesis of biobased and biodegradable aliphatic copolyesters from short building blocks. Effect of the monomer length. (December 2017) - Debuissy, Thibaud; Pollet, Eric; Avérous, Luc
Graphical abstract: Highlights: Lipase-catalyzed synthesis of PBSA and PPBS copolyesters under mild conditions. Increase of CALB activity with 1, 4-butanediol compared to 1, 3-propanediol. Similar CALB activity for diethyl succinate and diethyl adipate. Crystalline structures and thermal properties highly dependent on the architecture. Copolyesters with an isodimorphic co-crystallization behavior. Abstract: Biobased short aliphatic diols and diethyl carboxylates were enzymatically (co)polymerized in solution at mild temperature using the immobilized form of Candida antarctica lipase B (CALB) as biocatalyst. The influence of the monomer structure on the CALB activity was investigated. CALB showed a better affinity for 1, 4-butanediol compared to 1, 3-propanediol (1, 3-PDO), whereas no preference was observed between diethyl succinate and diethyl adipate. In addition, two series of random copolyesters [poly(butylene succinate- ran -butylene adipate) (PBSA) and poly(propylene succinate- ran -butylene succinate) (PPBS)] were synthesized at different compositions to investigate the effect of the composition on copolyesters, which were fully characterized by various chemical and physico-chemical techniques including NMR, SEC, WAXS, DSC and TGA. Their compositions were similar to the feed ones, despite the activity difference of the monomers towards CALB. Nevertheless, this activity difference resulted in the decrease of the Mw of PPBS from 24 to 11 kg/mol for 1, 3-PDO content varying from 0 to 100 mol.%. Moreover, 1, 3-PDO induced an increase of Tg and a decrease of the crystallization rate until having an amorphous behavior for high 1, 3-PDO content. On the other side, the reduction of the diethyl carboxylate chain length from diethyl adipate to diethyl succinate did not induce a clear tendency with Mn varying from 22 to 12 kg/mol with the succinate content. Furthermore, Tg increased with the succinate content and the good thermal stability of copolyesters were dependent on the diethyl carboxylates composition. Finally, both copolyesters exhibited an isodimorphic co-crystallization behavior.